Decline of Pulmonary Function Is Associated With the Presence of Rheumatoid Factor in Korean Health Screening Subjects Without Clinically Apparent Lung Disease: A Cross-Sectional Study - Hwang, Jiwon; Song, Jae-Uk; Ahn, Joong Kyong (Medicine (Baltimore), 2016)
Although higher-than-normal levels of rheumatoid factor (RF) are often observed in subjects without specific medical problems, little is known about the influence of RF on pulmonary function in health screening subjects. This study aimed to determine the association between the presence of RF and decreased pulmonary function in Korean health screening subjects without any history of joint disease or clinically apparent lung disease.A total of 115,641 study subjects (age range, 18-88 years) participated in the health checkup program. We excluded subjects who did not have pulmonary function test, as well as those with abnormal chest radiographs. Subjects with medical history of arthritis including rheumatoid arthritis, and lung disease based on the self-reported questionnaire. Final analysis was performed on 94,438 Koreans (41,261 women).RF-positive subjects had a lower forced vital capacity (FVC) predicted value and forced expiratory volume in 1 s (FEV1) predicted value than RF-negative subjects (82.8 ± 11.5% vs 83.8 ± 11.4% for FVC% predicted and 83.5 ± 13.0% vs 85.1 ± 12.9% for FEV1% predicted, P < 0.001 for both). RF positivity was significantly associated with the decline of FEV1% predicted regardless of smoking history (adjusted odds ratio [OR] = 1.289 [95% confidence interval [CI] 1.163-1.429], P < 0.001 for nonsmokers and adjusted OR = 1.138 [95% CI 1.004-1.289], P < 0.001 for smokers) while the decline of FVC% predicted only in nonsmokers (adjusted OR = 1.251 [95% CI 1.133-1.382], P < 0.001). Our results suggest that the presence of RF could impact pulmonary function in apparently healthy subjects. A follow-up study to investigate serial changes in pulmonary function may reveal the actual influence of raised RF titers.